Los recursos didácticos y su incidencia en el desarrollo creativo de los niños del primer año de educación básica de la escuela “Adonaí”, del cantón “Quevedo” provincia de los Ríos, periodo lectivo 2015-2016 - Gonzalez Burgos, Raquel Carolina (2015)
Teaching resources and their impact on the creativity of students, a simple definition of didactic resource, is any material that has been developed with the intention of facilitating the teacher's role and the student's turn. Let's not forget that teaching resources should be used within the educational context. The didactic resources provide information to the student. They are a guide for learning, as they help us organize the information we want to convey. In this way we offer new knowledge to the student. They help us to exercise the skills and also to develop them. The didactic resources awaken the motivation, impel and create an interest towards the content of the same awakening their creativity. The didactic resources allow us to evaluate the knowledge of the students in each moment